An Empirical Analysis of the Output Declines in Three Eastern European Countries : Volume 40 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1993)
The declines in economic activity experienced by Bulgaria, the Czech and Slovak Federal Republic, and Romania in the period since market-oriented reforms were initiated are analyzed. After reviewing developments in these three countries, the paper empirically investigates two questions that are central to an interpretation of the output decline. First, to what extent does the output fall reflect 'structural change,' or a reallocation of resources across sectors, rather than a conventional macroeconomic recession? Second, to what extent have demand-side or supply-side forces been dominant in generating the output decline?.